Complete blood picture with skeletal and visceral changes in patients with thalassemia major - Mehmood, Ramsha; Yaqoob, Uzair; Sarfaraz, Asma; Zubair, Ujala (International Journal of Health Sciences, 2018)
Objective: The objective of this to find the prevalence of skeletal and visceral changes in thalassemics and its relationship with variation in blood components. Methodology: This is a cross-sectional study conducted in tertiary care hospital in Karachi among patients diagnosed with thalassemia major who require regular blood transfusions. Result: Among 200 individuals, 95 were females, whereas 105 were males. 96.5% of the study sample showed normocytic normochromic blood picture. Mean pre-transfusion hemoglobin (Hb) for 200 patients was 8.91 g/dl, while the mean post-transfusion Hb was 12.07 g/dl. Among all the variables, some strong predictors of change were age and HbA which were found associated with the development of cardiac change in transfusion-dependent thalassemia patients. Hepatomegaly was observed in 66.5% of the patients while normal liver span was observed in 33.5%. 6% of patients showed evidence of skeletal changes on X-ray. Splenomegaly was observed in 26.5%, while in 4.5% of the patients, spleen was not visualized due to splenectomy. Cardiac involvement was observed in 8% of the patients on T2*magnetic resonance imaging. Conclusion: Visceral changes particularly hepatomegaly is very common among transfusion-dependent thalassemia patients. Blood studies for Hb and ferritin levels help to detect these changes when conventional investigations are not possible.